Analisis Perencanaan Strategis dalam Musyawarah Perencanaan Pembangunan Desa (Musrenbangdes) (Studi pada Desa Karduluk, Kecamatan Pragaan Kabupaten Sumenep) - Sahara, Nurul; Sholihah , Qomariyatus; Hidayati , Firda (Jurnal Ilmiah Administrasi Publik, 2024)
Musrenbangdes is a tool for planning rural development by involving active community participation, encouraging initiative and their role in development planning (Bottom-Up Planning). This annual forum aims to develop community initiative and active role in development planning in Karduluk Village. The aim of this research is to analyze how strategic planning is integrated in Musrenbangdes using John M. Bryson's strategic planning theory. This type of research is descriptive qualitative. This research method includes data collection through interviews with relevant stakeholders, direct observation, and analysis of documents related to development planning. The results of this research show that strategic planning in the Musrenbangdes in Karduluk Village is running quite effectively, but the results of the 2023 Musrenbangdes proposed program, which totals eight proposals, none of which have been realized, one of the program proposals that has a high level of urgency is asphalting village roads, but the proposal This was not realized the same as the previous year. The key role of village officials in identifying development priorities, overcoming problems and challenges and increasing the involvement of the Karduluk village community in the Musrenbangdes forum still needs to be strengthened. Efforts are needed to strengthen the ability of village officials to carry out development in villages more effectively, and community involvement can be increased in the development planning process through the Musrenbangdes forum.